Soft robotic hand prosthesis using reverse engineering and fast prototyping - Almeida, Hugo (2018)
The present work aimed to develop a soft robotic prosthesis of the human hand using reverse engineering and fast prototyping. This project arises in response to some limitations of the current conventional prostheses, namely aesthetic, mechanical and cost, that fail to fulfil the needs of its users, for example with soft objects. The hand prosthesis design involved the acquisition and processing of a medical image of the user's hand, followed by a modelling process which proved to be highly complex, and finally the obtainment of a real model (by 3D printing) of the prosthesis. The results obtained proved to be satisfactory in the approximation of the hand morphology, low cost and the designed mechanical properties. However, due to some technological limitations (the used 3D printers), and more specifically in the physical conception of the model, its functionality is yet to be proved with the pneumatic control.